(untitled) (Global Journal of Science Frontier Research, 2017)
Fast development of precision agriculture in last years requires detailed maps for precise application of lime, manure and mineral fertilizers. Two kinds of maps are required: a general, base map, and application maps of a particular inputs. The general base map should contain management zones, resuming all factors affecting field management and fertilization, such as the water bodies, trees and windbreaks in direct neighborhood of the field, field topography, soil texture to a depth of about 1m, organic matter content, overall assessment of moisture/drainage conditions on the field and other factors, which may affect field management in long-term period. The application maps regarding a particular applications of lime, manure and mineral fertilizers should be prepared using the current results of soil analyses and the base map before each input application. Variable N application during crop vegetation should take into account also the weather conditions in a period preceding the application and current canopy N status or yield predicted in a particular vegetation period. The scale/resolution of the maps for precision agriculture should be concordant with the technical possibilities of the equipment used for application of various materials on a particular farm.